Attachment and Enforcement on Wages and Salaries: A Comparative Study - Asayel Faisal Alharbi; Alhanouf Abdulaziz Alsulami (International Journal of Law Research and Studies, 2025)
This study aims to examine the adequacy of the legal regulation governing the attachment and enforcement of wages and salaries under the Saudi legal system. It adopts the analytical method by examining the relevant statutory provisions, particularly Article (4/21) of the Enforcement Law and its Implementing Regulations, to assess their adequacy in achieving a balance between enabling creditors to recover their rights and protecting debtors and their dependents from the negative consequences resulting from attachment and enforcement. The study also employs the comparative method as a supporting approach, by examining the regulation of wage and salary attachment in Algerian and French law to the extent required by the study. Accordingly, the main research question focuses on the extent to which the current regulatory framework achieves a balance between enabling creditors to recover their rights in cases involving high-income debtors and protecting low-income debtors and their dependents from the adverse effects of attachment and enforcement. To address this question, the study is divided into two chapters. The first chapter examines the concept of attachment and enforcement against the debtor’s assets, as well as the assets and amounts exempt from attachment and enforcement. The second chapter is devoted to the attachment and enforcement of wages and salaries, by defining their scope and analyzing the statutory rules governing their attachment and enforcement. The study concludes that the Saudi legislator generally prohibits the attachment and enforcement of wages and salaries, allowing it only by way of exception and within fixed limits depending on the type of debt, without considering differences in debtors’ income levels. The study therefore recommends reconsidering these fixed limits by adopting a more flexible framework based on progressive attachment rates according to the debtor’s income level, to achieve a better balance between the interests of both parties.